Three lateral divergent pinning for displaced supracondylar humerus fractures in children - Tamrakar, Rojan; Khanal, Ramod; Acharya, Balakrishnan M.; Pradhan, Nabees Man Singh; Shrestha, Suman Kumar (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Cross or two lateral pinnings are the most commonly done procedures for displaced supracondylar humerus fractures in children. A crossed pin is biomechanically stable than lateral pins, but associated with risk of iatrogenic ulnar nerve injury. Recent studies have shown stable fixation with three lateral pin construct. The purpose of this study was to evaluate the efficacy of three lateral divergent pinning for displaced supracondylar humerus fractures.Methods: Thirty five children with Gartland types III were treated between November 2012 and November 2013. Closed reduction and three lateral divergent pinning was done with image intensifier guidance. Patients were followed up for minimum 6 months. Radiological assessment was done to see union, proper pin placement and loss of reduction. Clinically, patients were assessed by using Flynn criteria.Results: There were 24 (68.6%) male and 11 (31.4%) female children between 2 to 13 years of age with displaced supracondylar fractures, left side 26 (74.3%) and right nine (25.7%) cases. All were successfully managed with closed reduction and three lateral divergent pins within 2-6 days of injury. One radial and one median nerve palsies sustained at injury recovered spontaneously. No iatrogenic nerve injuries occurred. A comparison of perioperative and final radiographs revealed no loss of reduction. Twenty-seven excellent, five good, two fair and one poor results on Flynn’s grading. One patient had a superficial pin-tract infection.Conclusions: Closed reduction with three lateral divergent pins is safe for stable fixation of displaced supracondylar humeral fractures in children.